2011
DOI: 10.2174/1874210601105010139
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Osteogenic Induction Of Human Gingival Fibroblasts For Bone Regeneration

Abstract: Background And Objective:Periodontitis is an inflammatory disease causing bone loss, and is a primary cause of tooth loss. Gingival fibroblasts are readily available with minimal donor site morbidity and may be ideal for tissue engineering efforts in regenerating lost alveolar bone. Dexamethasone (Dex) is commonly employed for in vitro osteogenic induction of a variety of cells, but its effect on human gingival fibroblasts (HGF) is still controversial. Therefore, the aim of our study was to investigate the ost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 28 publications
3
25
1
Order By: Relevance
“…These results are in agreement with literature data 15 but we have extended the range of concentrations evaluated up to 100 mmol L 21 , proving the non-cytotoxic effects of DXM and CS-PLGA NPs on HGFs.…”
Section: Dxm-loaded Nps Synthesis and Characterizationsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are in agreement with literature data 15 but we have extended the range of concentrations evaluated up to 100 mmol L 21 , proving the non-cytotoxic effects of DXM and CS-PLGA NPs on HGFs.…”
Section: Dxm-loaded Nps Synthesis and Characterizationsupporting
confidence: 92%
“…Alkaline Phosphatase (ALP) specific activity was used in this study (with Alizarin red assay), to verify the osteogenic differentiation of HGFs; this enzyme, in fact, was one of the first markers identified to assess the osteogenic phenotype. 25 Some papers have already demonstrated the ability of HGFs to differentiate as osteoblasts 13,15,24,26,27 whereas other authors showed opposed results. [28][29][30] Even if this topic is under debate, a recent review is also in favor of the ability of HGFs to assume the osteoblast phenotype, 27 thus for the purpose of the present study, this system is suitable to investigate the effect of DXM release from NPs.…”
Section: Dxm-loaded Nps Synthesis and Characterizationmentioning
confidence: 99%
“…ALP expression is reportedly higher at early stages of osteoblast differentiation peaking around days 14 or 15 [18, 20, 58]. In line with this notion, our study showed a decrease in ALP expression at day 21, indicating that maturation has progressed as also inferred from the upregulation in the expression of some of the later markers, such as osteopontin (OP), an extracellular structural protein responsible for mineralization of the ECM, and osteonectin (ON), a post-proliferative glycoprotein responsible for binding differentiated osteoblasts to the calcium found in the fully mineralized ECM, [59]. As seen in Figures 8C and D, while both CTS-GP and CTS-HA-GP scaffolds promote 7F2 cell maturation and differentiation, the cells cultured on the HA-containing scaffolds matured at a faster rate, evident by a sharp increase in ON and sharp decrease in OP mRNA from day 1 to day 14 on CTS-HA-GP scaffolds, as compared to the more gradual and linear increase on CTS-GP scaffolds (p < 0.01).…”
Section: Discussionsupporting
confidence: 78%
“…For example, chitosan nanofibers -reinforced poly(butylene succinate) microfibers induced osteogenic differentiation of human bone marrow derived MSC, as assessed by by the increased gene expression of ALP, OP, bone sialoprotein, osteocalcin, Runx2 and Osterix [57]. Similarly, chitosan containing poly(caprolactone) nanofibers promoted osteogenic maturation of MC3T3 mouse preosteoblasts over a 14 day period, as assessed from the enhanced gene expression of collagen 1 and OP in the presence of chitosan when compared to TCP and PCL alone [59]. In adding to this body of evidence for the usefulness of chitosan as base material for bone scaffolds, our study is the first to show that the presence of HA and crosslinking with GP significantly enhances the mechanical strength of electrospun CTS based nanofibrous scaffolds and their capacity to induce osteogenic differentiation of osteoprogenitor cells…”
Section: Discussionmentioning
confidence: 99%
“…Enjuanes et al (2005) used vitamin D and dexamethasone to stimulate an osteoblast cell culture from healthy bone fragments, obtaining good results in terms of osteoblast replication [5]. Their results showed that vitamin D and dexamethasone played a significant role as potential stimulators of CYP19 aromatase transcription.5 In addition to its antiinflammatory properties, dexamethasone also has the capacity to function as an immunosuppressant agent in vivo [6].…”
Section: Introductionmentioning
confidence: 99%